b - Pyles, D.G.; Rish, R.M.; Warner, J. (Charlotte, NC. : Information Age Publishing, Inc., 2019)
Digital literacy practices have often been celebrated as means of transcending the constraints of the physical world through the production of new social spaces. At the same time, literacy researchers and educators are coming to understand all the ways that place matters. This volume, with contributors from across the globe, considers how space/place, identities, and the role of digital literacies create opportunities for individuals and communities to negotiate living, being, and learning together with and through digital media. The chapters in this volume consider how social, cultural, historical, and political literacies are brought to bear on a range of places that traverse the urban, rural, and suburban/exurban, with emphasis placed on the ways digital technology is used to create identities and do work within social, digital, and material worlds. This includes agentive work in digital literacies from a variety of identities or subjectivities that disrupt metronormativity, urban centrism (and other -isms) on the way to more authentic engagement with their communities and others. Featuring instances of research and practice across intersections of differences (including, but not limited to race, class, gender, sexuality, ability, and language) and places, the contributions in this volume demonstrate the ways that digital literacies hold educative potential"
Includes references.
Keywords: Information society; Digital media -- Social aspects